Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Phương Dung

chứng minh rằng: (a+b+c)(ab+bc+ca)-abc= (a+b)(b+c)(c+a)

Nguyễn Thị BÍch Hậu
10 tháng 6 2015 lúc 20:46

\(\text{(a+b+c)(ab+bc+ca)-abc}=a^2b+ab^2+ac^2+ca^2+bc^2+cb^2+abc+abc+abc-abc\)

\(=ab\left(a+b\right)+c^2\left(a+b\right)+bc\left(a+b\right)+ca\left(a+b\right)=\left(a+b\right)\left(c^2+ab+bc+ca\right)\)

\(=\left(a+b\right)\left[c\left(c+b\right)+a\left(c+b\right)\right]=\left(a+b\right)\left(b+c\right)\left(c+a\right)\)=> đpcm


Các câu hỏi tương tự
vũ phúc
Xem chi tiết
Momozono Nanami
Xem chi tiết
zZz Phan Cả Phát zZz
Xem chi tiết
Lê Thiện
Xem chi tiết
JESSICA
Xem chi tiết
Nguyễn Thị Thu Trà
Xem chi tiết
Tiến Nguyễn Minh
Xem chi tiết
nguyễn thị hạnh
Xem chi tiết
Long
Xem chi tiết